Pengaruh pengetahuan investasi, manfaat motivasi, dan modal minimal investasi terhadap keputusan investasi di Pasar Modal - Fitriasuri Fitriasuri; Rahayu Maharani Abhelia Simanjuntak (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of investment knowledge, investment benefits, investment motivation and minimal capital on investment decisions by students. The population in this study is data from students majoring in accounting for the 2018 class from several universities in the city of Palembang with the help of the slovin method. While the sample data used were 85 respondents who came from students majoring in accounting. The data collection method used in this study is a qualitative method in which researchers distribute questionnaires that will be filled out by respondents using SPSS version 25 test equipment, Investment Benefits and Investment Motivation have no effect on Investment Decisions. While the Minimum Investment Capital affects investment decisions